On nonlinear boundary value problems with deviating arguments and discontinuous right hand side. (1993) - Dhage Dhage, B. C. B. C.; Heikkilä Heikkilä, S. S.
Abstract : In this paper we shall study the existence of the extremal solutions of a nonlinear boundary value problem of a second order differential equation with general Dirichlet/Neumann form boundary conditions. The right hand side of the differential equation is assumed to contain a deviating argument, and it is allowed to possess discontinuities in all the variables. The proof is based on a generalized iteration method.